“Todo texto desejaria não ser texto”: letra, corpo, vida com Ana Cristina Cesar - Moura, Amanda Jéssica Ferreira (2024)
Based on the formulation that “Every text would wish not to be a text”, by Ana Cristina Cesar, this research interrogates the aforementioned poet’s writing in its desire to be below or beyond the text. The investigation traverses through the formal composition and the reading effects of the corpus constituted especially of the poems published in the Malasartes (1975) magazine, in the 26 poetas hoje (1976) anthology, of the book A teus pés (1982), and of the posthumous work Caderno Portsmouth-Colchester (1989) — other writing records, such as Ana Cristina C’s essays, translations and letters, are also incorporated into the research. With theoretical and critical support of notions extracted from literary theory, psychoanalysis and philosophy, this study moves with the idea that Ana’s writing, in its desire to spill beyond the limits of the text, pursues in search of bliss and advances towards letter, body, life.